The Effectiveness of Historical Memes on High School Students' Interest in Learning History - Vaizin, Aris Nur (Universitas Negeri Semarang, 2023)
This research aims to: (1) Understand the history learning process for class in history learning at SMA Jakenan Pati (a High School); (2) Analyzing the effectiveness of history learning using historical memes at SMA Jakenan Pati; and (3) Knowing the influence of the use of historical memes on students' interest in learning history at SMA Jakenan Pati. This research uses a quantitative research method that uses an experimental research design. The research results show (1) teachers are good at teaching history but teachers do not use the facilities provided by the school such as wifi facilities, LCD projectors in each class. Teachers still use the lecture method; (2) The first indicator of respondents was doubtful at 20.75%, strongly agreed and agreed at 76.85%, and a small portion disagreed and strongly disagreed at 2.4%. The second indicator which discusses learning more quickly, effectively and efficiently shows that 29.44% are unsure, 67.56% strongly agree and 3% disagree; and (3) Based on the summery model table which has been analyzed using the SPSS 25 program, it shows that the R Square value is 0.228= 22.8%. These results show that the independent or non-free variable (historical memes) influences the independent variable (interest in learning) in history learning for class Meanwhile, the remaining 77.2% is explained by other factors not covered in this study.